CONSTITUTIONAL SUPREMACY IN LEGAL STATES IN INDONESIA - I Gusti Ayu Agung Dwi Candra; I G A Putri Kartika; I Nyoman Bagiastra (Transpublika Publisher, 2024)
The aim of this paper is to explore the significance of constitutional supremacy within the legal framework of Indonesia. The research methodology employed is normative legal research, utilizing both a statutory regulation approach and an analytical approach. Legal resources are accessed through library research techniques. The findings indicate that constitutional supremacy serves as the foundation for upholding constitutionalism, ensuring the sovereignty of the people. The future of constitutionalism hinges on the decisions made by the Constitutional Court, acting as the guardian of constitutional principles. Amendments to the 1945 Constitution, whether through formal or informal means, are crucial in solidifying Indonesia's status as a legal state. However, changes resulting from the ratification of international agreements may pose challenges by potentially undermining the constitution's authority. This could lead to conflicts between domestic laws and international obligations, creating a dilemma for the Government in balancing national interests with international commitments. Therefore, it is imperative to establish a robust judicial system to safeguard the supremacy of the constitution. Any constitutional interpretations must be shielded from political influences. A system of checks and balances among government institutions, along with a review of laws and regulations to ensure alignment with the 1945 Indonesian Constitution, is essential to uphold constitutional supremacy.